Combination of Endogenous Estradiol and Adipokine Leptin in Breast Cancer Risk and Prognosis Assessment in Postmenopausal Chinese Women - Luo, Yang; Li, Han-Bing; Zhang, Yue; Wu, Yu-Xin; Shen, Di; Che, Yi-Qun (Frontiers in Endocrinology, 2021)
Objective Our study aims to clarify the role of estradiol and leptin in breast cancer risk and prognostic assessment in postmenopausal Chinese women. Design The serum circulating estradiol and leptin level was detected by ELISA. Then the correlation between estradiol, leptin level, and clinical characteristics was analyzed using Fisher’s exact test. Next, the Kaplan-Meier model was used to analyze the association between estradiol, leptin, and prognosis of postmenopausal breast cancer patients in our cohort and the TCGA dataset. Setting The study was conducted at the National Cancer Center, Cancer Hospital, Chinese Academy of Medical Sciences, and Peking Union Medical College. Patients A total of 182 postmenopausal breast cancer patients and 111 healthy subjects from January 2010 to August 2010 were included in the analysis. Another 702 cases with breast cancer were retrieved from The Cancer Genome Atlas (TCGA) database for subsequent analysis. Main Outcome Measure Serum circulating estradiol and leptin level. Results The level of estradiol was significantly higher (P<0.001) but the level of leptin had no significant difference (P = 0.764) in postmenopausal breast cancer patients compared with healthy subjects. The level of estradiol and leptin was not significantly different between estrogen receptor (ER) positive and ER-negative groups (P>0.05). Estradiol was significantly correlated with tumor T stage (P = 0.002) and leptin was significantly associated with perineural invasion (P = 0.014). In addition, the disease-free survival of patients with a high level of estradiol was significantly shorter (P = 0.025) but leptin tended to be a protective factor for overall survival in TCGA analysis (P = 0.038). Conclusion Circulating estradiol and leptin played important roles in the risk of postmenopausal breast cancer even in low-estrogen nations with an independent expression of ER status. High circulating estradiol was a poor prognostic factor and leptin may be a protection signal in Chinese postmenopausal patients with breast cancer.